An epidemiological study of abdominal and pelvic injury trauma in post-mortem cases at Hospital Kuala Lumpur between the year of 2002-2003 - Abdul Halim Mansar; Muhammad Aadeel T.; Khairul Osman; Sharin Iskandar A.W. (Penerbit UKM, 2008)
The abdominal pelvic cavity has always been regarded as one of the most vulnerable regions of the body. Injuries to this part have been known to be very serious. Based on this a retrospective study was performed on postmortem cases with abdominal and pelvic trauma from 1 October 2002 to 31 January 2003 at the Forensic Institute, Hospital Kuala Lumpur to determine the common pattern of abdomino-pelvic injuries, the injury’s relationship to epidemiological and socio-economic factors, risk organ within the abdominopelvic region and relationship between injuries and survival period. A total of 122 cases abdomino-pelvic were obtained stemming from medico legal postmortems procedures. Results indicated that those aged between 21 to 30 years (38.5%) had the highest incidence of this type of injury. Categorization based on gender showed that males (90.2%) dominated most of the cases. Prevalence based on socio-economic status showed that lower socioeconomy class (52.5%) had the highest incident. This was followed by the middle income (39.3%) and finally the higher income group. The most numerous type of trauma was non-penetrating trauma (94.3%). It was also found that victims with low injury severity score (ISS) had a longer survival period as compared to those with high ISS. It was also noted that victims with two or more region injuries either were spot dead or brought dead. The most common combination of injuries was abdomen, pelvic, chest and limb. In most blunt trauma cases majority of victims had one or two organ involvement while penetrating injuries were difficult to asses. The most common organ involved in this type of trauma was liver (72.1%), pelvic bone (47.5%) and spleen (43.4%). In conclusion, abdomino-pelvic injury is a serious condition and should not be overlooked. Proper attention towards their diagnosis and management is important and so any patient of head injury with coma must be considered as having intra-abdominal injury until proven otherwise.